The impact of mandatory CSR disclosure on firm efficiency in an emerging country - Kieu, Thi-Khanh; Nguyen, Cong-Hoang; Wu, Shu-Hsing (Journal of Business Economics and Management, 2022)
The government in emerging economies often moves firstly in issuing regulations to push the firms follow some social commitments. Natural resource-based firms in Indonesia are the first movers to be required for mandatory CSR disclosure. This study explores how the efficiency of those firms was affected under such the regulations. The sample includes Indonesian firms listed on the Indonesia stock exchange in 2009–2019, and the data is analysed by data envelopment analysis and difference-in-differences method with 506 treatment and 2,536 control firm-year observations. The results express the positive impact of mandatory CSR disclosure on firm efficiency. This study also suggests the policy makers to provide clear standards in regulations, and consider expanding the applicable objects. Managers should utilize this regulation as an effective tool to develop and manage the companies’ annual plan, and improve firm performance.